Conceptual model for the formation of bedforms along subglacial meltwater corridors (SMCs) by variable ice‐water‐bed interactions - Vérité, Jean; Livingstone, Stephen; Ravier, Edouard; Mcmartin, Isabelle; Campbell, Janet; Lewington, Emma; Dewald, Nico; Clark, Chris; Sole, Andrew; Storrar, Robert (Earth Surface Processes and Landforms, 2024)
International audience Abstract Subglacial meltwater landforms found on palaeo‐ice sheet beds allow the properties of meltwater drainage to be reconstructed, informing our understanding of modern‐day subglacial hydrological processes. In northern Canada and Fennoscandia, subglacial meltwater landforms are largely organized into continental‐scale networks of subglacial meltwater corridors (SMCs), interpreted as the relics of subglacial drainage systems undergoing variations in meltwater input, effective pressure and drainage efficiency. We review the current state of knowledge of bedforms (hummocks, ridges, murtoos, ribbed bedforms) and associated landforms (channels, eskers) described along SMCs and use selected high‐resolution DEMs in Canada and Fennoscandia to complete the bedform catalogue and categorize their characteristics, patterning and spatial distributions. We synthesize the diversity of bedform and formation processes occurring along subglacial drainage routes in a conceptual model invoking spatiotemporal changes in hydraulic connectivity, basal meltwater pressure and ice‐bed coupling, which influences the evolution of subglacial processes (bed deformation, erosion, deposition) along subglacial drainage systems. When the hydraulic capacity of the subglacial drainage system is overwhelmed glaciofluvial erosion and deposition will dominate in the SMC, resulting in tracts of hummocks and ridges arising from both fragmentation of underlying pre‐existing bedforms and downstream deposition of sediments in basal cavities and crevasses. Re‐coupling of ice with the bed, when meltwater supply decreases, facilitates deformation, transforming existing and producing new bedforms concomitant with the wider subglacial bedform imprint. We finally establish a range of future research perspectives to improve understanding of subglacial hydrology, geomorphic processes and bedform diversity along SMCs. These perspectives include the new acquisition of remote‐sensing and field‐based sedimentological and geomorphological ...